Efficacy and safety of TCMs with anti-inflammatory effect in patients with rheumatoid arthritis: A network meta-analysis - Fang, Jinying; Liu, Mingxuan; Huang, Zhenghui; Ma, Yucao; Wang, Yiwen; Zheng, Xiaojia; Lv, Liu; Liu, Chunpin; Li, Wei; Zhu, Zhenghong; Zhu, Huachao; Hu, Jie; et al. (Frontiers in Immunology, 2023)
Abstract Background: Traditional chinese medicines (TCMs), such as Tripterygium wilfordii Hook F (TwHF), glycyrrhiza uralensis, caulis sinomenii and etc, have anti-inflammatory effect. They are widely used in China to treat Rheumatoid arthritis (RA), but proof of their use as an evidence-based medicine is little. The aim of this network meta-analysis (NMA) was to evaluate the efficacy and safety of TCMs. Methods: By searching online databases and using a manual retrieval method, randomized controlled trials (RCTs) that met specific selection criteria were included in the meta-analysis.The search included papers that were published between the establishment of the databases and November, 10, 2022. Analyses were performed using Stata software (version 14) and Review Manager (version 5.3). Results: 61 papers involving 6401 subjects and were enrolled into current NMA. For ACR20, MTX plus SIN therapy (94.30%) may be the significant choice. For ACR50 and ACR70, MTX plus IGU therapy (95.10%, 75.90% respectively) did better than other therapies. IGU plus SIN therapy (94.80%) may be the promising ways to reduce DAS-28, followed by MTX plus IGU therapy (92.80%) and TwHF plus IGU therapy (83.80%). In analysis of incidence of adverse events, MTX plus KX therapy (92.50%) had least potential, while LEF therapy (22.10%) may cause more adverse events. In the same time, TwHF therapy, KX therapy, XF therapy and ZQFTN therapy were not inferior to MTX therapy. Conclusions: TCMs with anti-inflammatory effect were not inferior to MTX therapy in treating RA patients. Combining with TCMs can improve the clinic efficacy and reduce the possibility of adverse events of DMARDs, which maybe a promising regimen.